SELF-IDENTIFICATION AS PREDICTOR OF PLEASURE READING AMONG STUDENTS OF UNIVERSITY-OWNED SENIOR SECONDARY SCHOOLS IN SOUTHWESTERN NIGERIA - Florence Adeola Omoba (Edulib, 2020)
Pleasure reading seems to be a fast eroding culture among senior secondary school students in Nigeria. Previous studies focused on reading habits but with little consideration for psychological factors that affect reading. This study therefore, investigated the extent to which self–identification predicted pleasure reading among students of university-owned senior secondary schools in Southwestern Nigeria. A total of 1,054 senior secondary school two students were selected from eight university-owned schools (Federal and State) in southwestern Nigeria were involved in the study.  The instruments used were: Pleasure Reading (r = 0.74) and Students’ Self-Identification (r = 0.73) scales. Data were analysed using descriptive statistics, Pearson Product Moment Correlation and Multiple regression analysis at 0.05 level of significance. Respondents had average level of pleasure reading (23.66) and high level of self-identification (53.10). The study discovered that higher the level of self-identification, the higher the level of pleasure reading. Other determining factors could have been responsible for average level of pleasure reading since the level of self-identification is high